Lameness in crossbred cows: Its effect on productive and reproductive performance - Tyagi, Kalpna (Indian Journal of Dairy Science, 2017)
Lameness is a common hoof disorder in dairy cows, significantly affects their productive and reproductive performances. Present study was conducted on 10 years (January, 2003 to December, 2012) lactation records of crossbred cows (n=1153). Overall lameness incidence in crossbred cows was 10.66% (123/1153). There was significant effect of parity on lameness (c2=17.9, df=4, P